Notch Signaling Activates Stem Cell Properties of Müller Glia through Transcriptional Regulation and Skp2-mediated Degradation of p27(Kip1) - Del Debbio, Carolina Beltrame (PLoS One, 2016)
Müller glia (MG), the sole glial cells generated by retinal progenitors, have emerged as a viable cellular target for therapeutic regeneration in degenerative blinding diseases, as they possess dormant stem cell properties. However, the mammalian MG does not display the neurogenic potential of their lower vertebrate counterparts, precluding their practical clinical use. The answer to this barrier may be found in two interlinked processes underlying the neurogenic potential, i.e., the activation of the dormant stem cell properties of MG and their differentiation along the neuronal lineage. Here, we have focused on the former and examined Notch signaling-mediated activation of MG. We demonstrate that one of the targets of Notch signaling is the cyclin-dependent kinase inhibitor (CKI), p27(Kip1), which is highly expressed in quiescent MG. Notch signaling facilitates the activation of MG by inhibiting p27(Kip1) expression. This is likely achieved through the Notch- p27(Kip1) and Notch-Skp2-p27(Kip1) axes, the former inhibiting the expression of p27(Kip1) transcripts and the latter levels of p27(Kip1) proteins by Skp2-mediated proteasomal degradation. Thus, Notch signaling may facilitate re-entry of MG into the cell cycle by inhibiting p27(Kip1) expression both transcriptionally and post-translationally.